2011
DOI: 10.1093/brain/awr053
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal sclerosis in advanced age: clinical and pathological features

Abstract: Hippocampal sclerosis is a relatively common neuropathological finding (∼10% of individuals over the age of 85 years) characterized by cell loss and gliosis in the hippocampus that is not explained by Alzheimer's disease. Hippocampal sclerosis pathology can be associated with different underlying causes, and we refer to hippocampal sclerosis in the aged brain as hippocampal sclerosis associated with ageing. Much remains unknown about hippocampal sclerosis associated with ageing. We combined three different lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
371
7
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 235 publications
(413 citation statements)
references
References 71 publications
29
371
7
2
Order By: Relevance
“…Neuropathologic studies reveal the abnormal accumulation of TAR-DNA binding protein 43 (TDP-43) in a pattern distinct from frontotemporal lobar degeneration. 20 Of clinical relevance, patients with hippocampal sclerosis tend to have less significant functional impairment than patients with Alzheimer disease. 21 Effective evaluation of a patient with an episodic memory concern requires a collateral historian.…”
Section: Key Pointsmentioning
confidence: 99%
“…Neuropathologic studies reveal the abnormal accumulation of TAR-DNA binding protein 43 (TDP-43) in a pattern distinct from frontotemporal lobar degeneration. 20 Of clinical relevance, patients with hippocampal sclerosis tend to have less significant functional impairment than patients with Alzheimer disease. 21 Effective evaluation of a patient with an episodic memory concern requires a collateral historian.…”
Section: Key Pointsmentioning
confidence: 99%
“…In contrast, hippocampal sclerosis of aging (HS‐Aging) is considered as a distinct, dementia‐related pathology 18, 31, 35, 56, 58, neuropathologically characterized by severe neuron loss and gliosis in the CA1 area. The subiculum may be affected, but CA4, CA3 and are CA2 spared 16, 41, 43.…”
Section: Introductionmentioning
confidence: 99%
“…TDP-43 associates with the mRNA splicing and translational machinery (Freibaum et al 2010). Dominant mutations of the TARDBP gene were later found in familial ALS cases (Kabashi et al 2008;Sreedharan et al 2008;Van Deerlin et al 2008), and aggregation of TDP-43 is found in most cases of hippocampal sclerosis associated with aging (Nelson et al 2011) and in many cases of FTLD (Sieben et al 2012). The role of RBPs in ALS solidified with the discovery that dominant mutations of FUS also cause familial ALS (Kwiatkowski et al 2009;Vance et al 2009).…”
Section: Introductionmentioning
confidence: 99%